BIAYA KEPATUHAN PAJAK: PEMETAAN LITERATUR DAN POTENSI PENELITIAN LANJUTAN - Muamarah, Hanik Susilawati; Marsono, Marsono (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract— This study aims to investigate the methodological mapping in research on tax compliance costs, as well as to identify relevant further research topics. Information about theories used, measurement methods, research approach, and research context give important insight to identify research gaps and potential methodological developments. Use Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach in literature review, we analyzed 82 articles in the Scopus database from 1993 to 2023. The mapping results show various measurement techniques regarding the costs of tax compliance consisting of internal, external, incidental, psychological, and corruption costs, various theories used, types and contexts of research. The identification shows that there are still few studies with mixed methods and qualitative approaches, as well as difficulties in measuring costs, especially psychological costs. These findings shed light on the need to develop measurements for costs that are difficult to observe directly such as psychological costs, and exploring variables relate to tax compliance cost such as information technology. Exploring compliance costs in the context of MSMEs in both single-country and cross-country studies, especially when regulatory changes occur, and examining the impact of regulatory complexity on tax compliance costs for companies listed on the stock exchange, also another venue of research. Keywords: Tax Compliance Cost; Literature Review; Methodology; MSMEs; PRISMA.